Effects of teacher characteristics on Project ABC outcomes in Niger - Schutte, Rebecca F. (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: This paper provides the results of an impact evaluation measuring the effect of observable teacher characteristics (gender, age, local status and years of schooling) on Project ABC outcomes. Project ABC is a randomized mobile phone adult education program which taught participants basic mobile phone skills along with traditional literacy and math classes in two regions of Niger. Female teachers were associated with lower test scores overall, although this is highly correlated with the fact that female teachers mostly taught female students who had lower scores than males, on average. For teacher age, we see that younger teachers are better at teaching technology (target age for teachers is 28 to 33 years old) in ABC literacy classes, whereas older teachers (target age is 37 to 45 years old) are better at teaching ABC math which uses more traditional methods. Local teachers (teachers from the village where they were teaching) have a positive effect on ABC scores in Dosso, but a negative effect in Dosso overall and in Zinder. Teachers should have at least 7 years of schooling in order to have the greatest impact on student test scores.